2021
DOI: 10.1021/jacs.1c07571
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Jump Kinetics of Liquid–Liquid Phase Separation: Comparison of Two Different Condensed Phases of the RNA-Binding Protein, Fused in Sarcoma

Abstract: The RNA-binding protein fused in sarcoma (FUS) undergoes liquid–liquid phase separation (LLPS) both in vivo and in vitro. Self-assembled liquid droplets of FUS transform into reversible hydrogels and into more irreversible and toxic aggregates. Although LLPS can be a precursor of irreversible aggregates, a generic method to study kinetics of the formation of LLPS has not been developed. Here, we demonstrated the pressure-jump kinetics of phase transition between the 1-phase state and FUS-LLPS states observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Our previous high-pressure studies showed that interconversion among the two LLPS states and the one-phase state occurs in equilibrium, with the formation and disappearance of the LLPS states being reversible, whereas the formation and disappearance rates of HP-LLPS are 2- and 20-fold slower than those of LP-LLPS, respectively. 16,17 In the present study, we found that the liquid-to-solid phase transition that occurs over tens of hours under the LP-LLPS condition occurs within tens of minutes for HP-LLPS. Moreover, the droplets in HP-LLPS tend to strongly form clusters, followed by non-spherical aggregates, similar to that with the patient-type FUS variant.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Our previous high-pressure studies showed that interconversion among the two LLPS states and the one-phase state occurs in equilibrium, with the formation and disappearance of the LLPS states being reversible, whereas the formation and disappearance rates of HP-LLPS are 2- and 20-fold slower than those of LP-LLPS, respectively. 16,17 In the present study, we found that the liquid-to-solid phase transition that occurs over tens of hours under the LP-LLPS condition occurs within tens of minutes for HP-LLPS. Moreover, the droplets in HP-LLPS tend to strongly form clusters, followed by non-spherical aggregates, similar to that with the patient-type FUS variant.…”
Section: Discussionsupporting
confidence: 54%
“…S1, ESI†). 17 In contrast, the disappearance of the droplets was incomplete when the time spent in HP-LLPS was increased to 30–120 min (Fig. 2B).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations